The Effect of Home Bleaching on Color Match with Anterior Single Shade Composite Restoration - Buse Kesgin; Özhan Yağcı; Pınar Güvenç; Gamze Paken; Merve Ünal (Selcuk Dental Journal)
Background: Aim of this study is to assess the color matching in class III restorations made with single-shade resin composite after bleaching with different carbamide peroxide concentrations. Methods: In this study, 20 human incisors that were free of caries or enamel abnormalities and freshly extracted for periodontal or orthodontic reasons were cleaned of blood, debris, and calculus. Mesial and distal surfaces were restored with single-shade composite (Omnichroma, Tokuyama, Japan). All samples were randomly divided into two groups, all of the mesial surfaces were isolated, and distal surfaces were coated with %10 and %15 carbamide peroxide (Opalescence PF; Ultradent Products, Inc, USA). Polishing discs (Zenit Flex, President Dental, Germany) were used the composite restoration. Color matching was evaluated on photographs with a digital colorimeter. SPSS software program was used to perform statistical analysis (IBM Corp., Armonk, NY, USA). Results: Statistically significant difference was found between the color matching of the restorations after the 5th treatment with 15% carbamide peroxide (p = 0.004), and at the end of 10th treatment with 10% carbamide peroxide (p = 0.028). Depending on the carbamide peroxide concentration, after the 5th treatment a statistically significant difference was found between 15% and 10% carbamide peroxide (p = 0.000), but no statistically significant difference after the 10th treatment (p > 0.05). Conclusions: After carbamide peroxide bleaching, hard tissue color became lighter. Since there is no color pigment in single-shade composites, color might be lighter after bleaching. Therefore, these composites may be considered safer in bleaching. Keywords: Bleaching, Color Match, Composite